CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) AND THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This paper explores the synergy between Content and Language Integrated Learning (CLIL) and Information and Communication Technologies (ICT) in the context of modern education. CLIL represents a dual-purpose pedagogical framework where learners acquire subject-specific knowledge while simultaneously developing foreign language proficiency. ICT, on the other hand, provides digital instruments that enhance interaction, accessibility, and innovation in the learning process. By examining the theoretical underpinnings of CLIL, evaluating ICT-supported teaching strategies, and discussing both benefits and potential limitations, this study demonstrates that technology-enriched CLIL fosters learner autonomy, linguistic competence, and essential 21st-century skills. The outcomes of this analysis are particularly relevant to language pedagogy, teacher education, and curriculum modernization.